Prinsip Kesantunan Berbahasa dalam Penyampaian Berita oleh Valentinus Resa di Akun Tiktok Metro TV - halimahtus sadiyah; Mimas Ardhianti (sarasvati, 2026)
This research is motivated by the transformation of news delivery styles on TikTok, which tend to be informal and expressive. The phenomenon on the Metro TV TikTok account shows that the use of a satirical style by Valentinus Resa effectively attracts audience attention, yet still needs to be examined from the perspective of linguistic politeness. This study aims to describe the forms and functions of linguistic politeness principles within those narratives using a qualitative approach with a descriptive method. The data for this research consist of utterances by Valentinus Resa sourced from news videos uploaded to the official Metro TV TikTok account. Data were collected through documentation, observation, and note-taking techniques, then analyzed based on the communicative context. The results of the study show that the forms of politeness applied include six maxims consisting of the Tact Maxim, the Generosity Maxim, the Approbation Maxim, the Modesty Maxim, the Agreement Maxim, and the Sympathy Maxim These forms are manifested through various linguistic units, including word choice, phrases, terms, metaphors, and comparisons. In addition, two strategic functions of politeness in the narrative were found, namely the function of criticizing and the function of presenting factual information to the audience. The satirical and humorous style of news delivery proved to remain within the principles of politeness without offending the audience. The research conclusion revealed that this strategy allows critical news messages to be well received by the public through a more flexible and communicative approach without neglecting linguistic ethics.